Toward Digital Pedagogical Buffering: Grade 1 Teachers’ Perceptions of Language-Learning Applications in South Africa - Manditereza, Blandina (Al-Athfal: Jurnal Pendidikan Anak, 2026)
Purpose – This study describes Grade 1 teachers’ self-reported perceptions of digital applications in early language learning and examines whether the descriptive response pattern can inform Digital Pedagogical Buffering as a provisional interpretive concept.Design/methods/approach – A quantitative cross-sectional survey was completed by 43 Grade 1 language teachers from participating English-medium Quintile 4 and 5 public schools in the Free State, South Africa. The 12-item, five-point Likert questionnaire was reviewed by two specialists, piloted for clarity, and produced an overall Cronbach’s alpha of 0.82. This article reports means and standard deviations for six items directly aligned with its focus.Findings – Participants generally reported using digital applications in Grade 1 language instruction (M = 3.93, SD = 0.90). They also expressed positive perceptions of the contribution of digital applications to vocabulary development (M = 4.02, SD = 0.90), general language learning (M = 3.91, SD = 0.95), pronunciation (M = 3.89, SD = 0.89), and comprehension (M = 3.79, SD = 0.86). However, responses to the statement that digital tools may disturb natural language learning produced a lower mean and the greatest variability (M = 3.39, SD = 1.04), indicating less uniformity in teachers’ views of the pedagogical boundaries of digital technology. These differences are descriptive and were not tested inferentially.Research implications/limitations – The purposive and geographically bounded sample, reliance on self-reported perceptions, reporting of six selected questionnaire items, absence of response-distribution analysis, and lack of direct measures of technology acceptance, technological pedagogical content knowledge, classroom practices, or learner outcomes constrain the conclusions. The findings therefore illuminate perceived pedagogical value and tension rather than actual technology use, deliberate restriction, buffering behaviour, or instructional effectiveness.Practical implications – Teacher education and professional development should move beyond promoting increased technology use and instead strengthen teachers’ capacity to evaluate when, why, and how digital applications support language objectives, classroom interaction, oral communication, and multilingual meaning-making. This principle is relevant to education systems in the Global South and worldwide where digital expansion must be balanced with context-sensitive, relational, and language-responsive pedagogy.Originality/value – Digital Pedagogical Buffering is retained as a provisional interpretive lens, not a validated behavioural construct. It directs attention to the possibility that favourable technology perceptions may coexist with caution about the pedagogical reach of digital applications in socially mediated language learning.Paper type Research paper